Exploring users’ insights on chatbots experiences within Online Travel Agency (OTA) / Nurul Syafiqqah Mohammad Shawal ... [et al.] - Mohammad Shawal, Nurul Syafiqqah; Othman, Zulhan; Kedin, Nor Adila; Abdul Aziz, Azdel; Saiful Bakhtiar, Mohd Faeez (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2024)
Continuous technological automation through Artificial Intelligence (AI) is changing the frontline services within the hospitality and tourism industry. Chatbots is an AI based automated program featuring human-like interaction via chat or voice assistant with the customers; and it can be found in numerous service-based websites and mobile apps including Online Travel Agency (OTA). Understanding users’ ( or customers’) chatbots experiences is critical to ensuring its’ success implementation within the customer service field. Despite the growing number of hospitality and tourism firms adopting chatbots to delivering customer care, little attention has been paid towards chatbots users’ reaction, particularly from the OTA standpoint. Underpinning Technology Acceptance Model, this paper examined chatbots’ antecedents covering perceived ease of use (PEOU), perceived playfulness (PP) and perceived usefulness (PU); towards users’ experience and satisfaction in OTA. It was found that chatbots’ perceived playfulness (PP) and perceived usefulness (PU) affect customer experience in OTA; while chatbots experience mediates the relationship between perceived playfulness (PP) and perceived usefulness (PU) towards customer satisfaction in OTA. Outcome from this study is hoped to facilitate both the academicians and practitioners whom are promoting AI within the digital business environment particularly in the hospitality and tourism services.